Competences and learning outcomes: a panacea for understanding the (new) role of Higher Education? - Robert Wagenaar (Universidad de Deusto, 2014)
The competence and learning outcomes approach, which intends to improve effective performance of academic staff and students, is becoming dominant in today's higher education. This was quite different 15 years ago. This contribution aims to offer insight in the reforms initiated and implemented, by posing and answering the questions why the time was appropriate - by identifying and analysing the underlying conditions - and in what way the change was shaped - by focusing on terminology required and approaches developed. Central here is the role the Tuning project - launched in 2000-2001 - played in this respect. The contribution starts with contextualising the situation in the 1990s: the recession and growing unemployment in many European countries on the one hand and the development of a global society and the challenges the higher educational sector faced at the other. It offers the background for initiating the Tuning project, and the discourse on which its approach is based. In particular, attention is given to choosing the concept of competences, distinguishing subject specific and general/generic ones, as an integrating approach of knowledge, understanding, skills, abilities and attitudes. The approach should serve as a means of integrating a number of main goals as part of the learning and teaching process: strengthening employability and preparing for citizenship besides personal development of the student as a basis for the required educational reform. Tuning's unique contribution is the alignment of this concept to learning outcomes statements as indicators of competence development and achievement and by relating both concepts to profiling of educational programmes.